Schicksal, Fügung, Gott - Fischer, Klaus P. (Zeitschrift für katholische Theologie, 2011)
Suffering from events he cannot understand, man is condemned to either wretched or heroic resignation in the face of earthly catastrophes or, alternatively, may find himself invited, even challenged to accept help and comfort by the biblical revelation of God who discloses himself not as the cause of an incomprehensible fate, but as being the friend, lover and creator of life, calling and appointing man to be his partner in His bringing forth a good, right and just world, in the fight against the awful powers of darkness, fear, hate and death. The biblical Good News assures that God himself is being at work at making good and fulfilling His creation by vindicating believers from the troubles and tremors of their lives.